Multi-tracing of recharge seasonality and contamination in groundwater: a tool for urban water resource management - Vystavna, Yuliya; Schmidt, S.I.; Diadin, D.; Rossi, P.; Vergeles, Y.; Erostate, M.; Yermakovych, I.; Yakovlev, V.; Knoller, K.; Vadillo-Pérez, Iñaki (Elsevier, 2019)
In this study, sources of recharge and contamination in urban groundwater and in groundwater un- derneath a forest in the same aquifer were determined and compared. Data on hydro-chemical pa- rameters and stable isotopes of water were collected in urban and forest springs in the Kharkiv region, Ukraine, over a period of 12 months. Groundwater transit time and precipitation contribution were calculated using hydrogeological data and stable isotopes of water to delineate groundwater recharge conditions. Hydro-chemical data, stable isotopes and emerging contaminants were used to trace anthropogenic groundwater recharge and approximate sewage and tap water contributions to the aquifer. The results indicated that each spring had unique isotopic signatures that could be explained by recharge conditions, groundwater residence time, and specific mixing patterns with sewage and water leaks. Elevated nitrate content, stable isotopes of nitrate, and the presence of emerging pollutants (mainly illicit drugs) in most of the urban springs confirmed mixing of urban groundwater with sewage leaks. These leaks amounted to up to 25% of total recharge and exhibited seasonal variations in some springs. Overall, the results show that urban groundwater receives variable seasonal contributions of anthropogenic components that increase the risk to the environment and human health, and reduce its usability for drinking water production. The multi-tracing approach presented can be useful for other cities worldwide that have similar problems of poor water management and inadequate sewage and water supply infrastructure.
Keywords: Aguas subterráneas - Contaminación; Urban hydrology; Stable isotopes; Emerging compounds; Aquifer; Nitrate; Pesticide